Associations Between the Prevalence of Metabolic Syndrome and Sleep Parameters Vary by Age - Titova, Olga E.; Lindberg, Eva; Elmståhl, Sölve; Lind, Lars; Schiöth, Helgi B.; Benedict, Christian (Frontiers in Endocrinology, 2018)
Objective: To examine whether the relationship between the metabolic syndrome (MetS) and various sleep parameters (sleep duration, symptoms of sleep-disordered breathing (SDB), and sleep disturbances) varies by age. Methods: Waist circumference, blood pressure, triglycerides, HDL cholesterol, and fasting glucose were used to determine MetS status in a cohort (N=19,691) of middle-aged (aged 45-64y) and older (aged ≥ 65y) subjects. Habitual sleep duration (short, ≤6h/day; normal, 7-8h/day; and long, ≥9h/day), sleep disturbances (such as problems with falling and staying asleep), and symptoms of sleep-disordered breathing (SDB, such as snoring and sleep apneas) were measured by questionnaires. Results: Among the participants, 4,941 subjects (25.1%) fulfilled the criteria for MetS. In the entire sample, both short and long sleep durations were associated with higher prevalence of MetS as compared to normal sleep duration. When stratified by age, a similar pattern was observed for middle-aged subjects (<65 years old; prevalence ratio (PR) [95%CI], 1.13 [1.06-1.22] for short sleep and 1.26 [1.06-1.50] for long sleep duration). In contrast, in older individuals (≥65 years old), only long sleep duration was linked to a higher prevalence of MetS (1.26 [1.12-1.42]; P< 0.01 for sleep duration*age). In the entire cohort, having at least one SDB symptom ≥4 times per week was linked to an increased prevalence of MetS; however, the PR was higher in middle-aged subjects compared with older subjects (1.50 [1.38-1.63]) vs. 1.36 [1.26-1.47], respectively; P<0.001 for SDB*age). Finally, independent of subjects’ age, reports of sleep disturbances (i.e., at least one symptom ≥4 times per week) were associated with a higher likelihood of having MetS (1.12 [1.06-1.18]; P> 0.05 for sleep disturbance*age). Conclusion: Our results suggest that age may play a role in some associations between the prevalence of MetS and sleep parameters.